Pengembangan Jiwa Kewirausahaan dalam memanfaatkan potensi lokal untuk pemberdayaan UMKM: Sukoanyar, Kecamatan Wajak, Kabupaten Malang, Provinsi Jawa Timur - Indah Datin Nadliroh; Budi Iriani Yudaningrum (JOURNAL INNOVATION AND COMMUNITY SERVICE, 2023)
The aim of this service is to describe the development of entrepreneurship based on local potential through community empowerment, which consists of several stages including training, production, and marketing processes, as well as the obstacles experienced. This research uses a qualitative approach, using primary data collected through interviews, observation, and documentation. The research subjects consisted of residents studying Package C at PKBM Cipta Karya Sukoanyar, Wajak District, Malang Regency, East Java Province, and the informants were community leaders. The validity of the data depends on the triangulation of sources, methods, and theories. Data analysis as an interactive model includes data collection, reduction, presentation, and drawing conclusions. This dedication resulted in an empowerment program in the development process, which carried out training in making watches from wood. Production is carried out by residents studying Pursue Packages B and C after completing the pursuit of package learning. Marketing is carried out through promotions in various media and market share both at home and abroad. The obstacles experienced by the lack of production machines stem from the lack of capital and limited working hours for students studying